Imigração haitiana: um olhar antropólogico a partir do contexto do trabalho informal em Manaus-AM - Lima, Aurinéia Aiambo (2019)
This study is an anthropological research on Haitian immigration to Manaus-AM. The aim of the researchis to analyze the current context in which the Haitian immigrants find themselves, emphasizing the informal work in the context of Amazonian capital. Through the ethnographic method, as well as the participant observation and semistructured interview, the research also focused on other dimensions of the Haitian migratory phenomenon, focusing its attention on the social ties established between them in different contexts and especially at work. Here is taken as starting point the category of immigrant proposed by Abdelmalek Sayad as merely a workforce and the concept of diaspora placed by Joseph Handerson, understood by him as a matter of cultural identity. In general terms, considering that the Haitians in Manaus do not selfidentify themselves as immigrants neither as refugees, the condition of work, specifically that of the informal work, causes different strategic actions by them, also the appropriations of such categories, resulting, then, in a context in which they oscillate between the refugee, the immigration and the diaspora.